Addition of organic fertilizer affects soil nitrogen availability in a salinized fluvo-aquic soil. Issue 1 (1st January 2019) - Wang, Xiao-Wen; Cai, Hui; Liu, Yan-Li; Li, Cheng-Liang; Wan, Yong-Shan; Song, Fu-Peng; Chen, Wei-Feng
ABSTRACT: Organic matter application was one of the suitable ways to improve soil nitrogen availability in saline soils. In this study, two soils of different levels of total soluble salts, 2.45 g kg −1 (LS) and 4.03 g kg −1 (HS), were used in a pot experiment with eight treatments: bio-organic fertilizer (prepared with cow dung) and farmyard manure (fowl manure) each at three dosages (3350, 6700, and 13, 400 kg ha −1 ), chemical fertilizer control (DAP: 1675 kg ha −1 ), no fertilizer blank. At the same time, an indoor nitrogen mineralization incubation experiment with the same treatments without alfalfa planting was carried out. We aimed to explore the effects of the types and application amounts of organic fertilizers on soil nitrogen mineralization in saline soils and to improve its quality and finally realize its sustainable utilization. The main conclusions are as follows: the biomass of alfalfa treated with medium dose of organic fertilizer was higher than that of alfalfa treated with low or high dose of organic fertilizer. Compared with farmyard manure, bio-organic manure was more effective in increasing the biomass of alfalfa. The nitrogen uptake of alfalfa in high-dose treatment was significantly higher than that in low-dose treatment. The effects of the fertilizer treatments on soil nitrogen availability were in the increasing order of: medium dose, high or low dose of fertilizer treatment, single chemical fertilizer, and fertilizer free treatments by principal component analysis. For possible potential application, medium dosage of bio-organic fertilizer was recommended to apply in the region with saline fluvo-aquic soil.